Comparative evaluation of the efficiency of canine retraction using modified Marcotte and T-loop retraction springs - A split-mouth, randomized clinical trial - Shijo Davis; Shobha Sundareswaran; Jean James (Wolters Kluwer Medknow Publications, 2019)
OBJECTIVE: The aim of this study was to compare the efficiency of canine retraction using modified Marcotte and T-loop retraction springs. MATERIALS AND METHODS: Twenty-four subjects with a treatment plan involving bilateral extractions of upper first premolars were included in the study. A split-mouth design was used to randomly allocate opposite quadrants to either modified Marcotte spring (MS) or T-loop spring (TLS) for canine retraction. Cephalometric radiographs and models were used to measure the rate of canine retraction (primary outcome) and compare the angular/rotational changes in the canines and anchorage loss in molars (secondary outcomes) following retraction. Subjective assessment of pain and discomfort was compared using visual analog scale (VAS). Paired and independent t-tests were used to evaluate changes. RESULTS: The mean amount and rate of retraction of the canine were found to be significantly higher for MS (3.56 ± 0.696 mm and 1.188 ± 0.232 mm, respectively) when compared with TLS (2.125 ± 0.472 mm and 0.71 ± 0.157 mm, respectively). Distopalatal rotation of the canine was also significantly lesser for MS (2.42°±1.868°) than TLS (5.65° ±2.84°, P < 0.001). However, the amount of anchorage loss and canine tipping were significantly higher for MS. Statistically significant higher values in the VAS score for TLS indicated greater discomfort. CONCLUSION: MS exhibited increased rate of retraction and rotation control when compared with TLS during sectional canine retraction. Patient comfort was better for MS as evidenced by the VAS scores. However, the amount of tipping and anchorage loss obtained with MS were significantly higher than TLS.